Explore the Values of Pancasila as the Basic Philosophy of the Indonesian Nation - Sudirta, I Wayan; Pieris, John; Nugroho, Wachid; Ryantoni, Hanugra (Universitas Brawijaya, 2025)
This research explores the values of Pancasila in three approaches: beliefs, knowledge and action dimension. Legal construction and deconstruction methods are used in this research. Some previous studies that distinguish this research, Nataliana, et.al (2022) discusses Pancasila within the scope of the Indonesian maritime state, Izzati and Muslikhah (2024) analyses Pancasila as the philosophy of the Indonesian nation, and Junia, et.al (2025) explores Pancasila in its level as an ideology and state philosophy. The striking difference from this research is the depth of discussion about Pancasila in this journal to find findings related to the foundation of Pancasila as the philosophy of the Indonesian state. The values in Pancasila developed along with the formulation by the founding fathers, but remained at the root of Soekarno’s conception that Pancasila as Philosofische Grondslag and as Weltanschaung. In Pancasila there are values that contain cultural values (the first, second and third precepts), political values and mutual cooperation (fourth precept), and material values and justice (fifth precept). All of these values have not been the basis of work and the preparation of policy platforms in all lines and Indonesian state administration. The contribution of research to legal science can be seen from the position of Pancasila as a state ideology that is explored more deeply in this research in order to explore its values as the basis of the Indonesian nation and become a reflection for other countries in exploring the philosophical values of their state ideology.